184k views
4 votes
Select the simplification that accurately explains the following statement.

Thank you.

Select the simplification that accurately explains the following statement. Thank-example-1

2 Answers

2 votes

(9 ^ (1/2)) ^ 2 = (9 ^ (1/2)) * (9 ^ (1/2)) = (9) ^ (1/2 + 1/2) = (9) ^ (2/2) = (9) ^ (1) = 9

User Vincent Savard
by
6.1k points
2 votes
The answer for this case is number one.
Remember that by properties of exponents:
Same basis, the exponents are added.
We have then the following:
(9 ^ (1/2)) ^ 2 = (9 ^ (1/2)) * (9 ^ (1/2)) = (9) ^ (1/2 + 1/2) = (9) ^ (2/2) = (9) ^ (1) = 9
answer
number one.
User Carla
by
5.2k points